Femoral neck-specific cortical thickness predicts internal fixation complications across adults with implications for elderly surgical decision-making - Zhiyuan Fan; Bohao Yin; Chenjun Liu; Hui Sun; Wei Zhang (Frontiers in Medicine, 2026)
Background Chronological age is an unreliable sole criterion for selecting internal fixation (IF) versus arthroplasty in femoral neck fractures (FNFs). This study evaluated whether the femoral neck cortical thickness index (FN-CTI), a CT-based measure of local bone quality, predicts complications after internal fixation in patients spanning a wide age range. We placed particular emphasis on the utility of FN-CTI for decision-making in elderly patients and also assessed whether a composite risk score could further enhance clinical decision-making. Methods We retrospectively analyzed 219 FNF patients treated with IF (minimum 24-month follow-up). Independent predictors were identified via multivariable Cox regression. Receiver operating characteristic (ROC) curves, Net Reclassification Improvement (NRI), and Decision Curve Analysis (DCA) were used to evaluate performance and clinical utility. A point-based risk score was constructed from regression coefficients. Results Complications occurred in 47 patients (21.46%). FN-CTI (per 0.1 increase: HR = 0.059, p < 0.001), modified Pauwels angle (HR = 1.035, p = 0.026), and BMI (HR = 1.106, p = 0.023) were independent predictors. FN-CTI achieved an AUC of 0.723 (cutoff: 0.12). The composite risk score (0--5 points) stratified patients into low- and high-risk groups with log-rank p < 0.001. DCA confirmed superior net benefit across clinically relevant threshold probabilities. Conclusion In this derivation cohort, lower FN-CTI was independently associated with a higher rate of mechanical complications after internal fixation in adults with femoral neck fractures. The same direction of effect was observed in the small elderly subgroup. The composite score improved risk stratification compared with individual predictors alone. However, whether high-risk patients would benefit from primary arthroplasty remains unknown and requires future comparative studies. Prospective external validation is required before clinical adoption, particularly in unselected older populations. Trial registration This retrospective cohort study was approved by the institutional review board of our center and registered at www.chictr.org.cn (ChiCTR1900023156).